EXPLORING MARITIME CADETS’ ANXIETY IN ENGLISH SPEAKING - Desy Intan Fathiah; Usman Kasim; Siti Sarah Fitriani (Universitas Syiah Kuala, 2020)
This research was aimed at measuring the level of cadets’ anxiety in speaking English and finding out the dominant aspects of speaking anxiety faced by maritime cadets at Malahayati Merchant Marine College. To obtain this objective, the study was conducted at Malahayati Merchant Marine College. The participants of this study were 174 second-semester cadets at Malahayati Merchant Marine College and 15 English teachers. The data were obtained through questionnaires. Descriptive quantitative was used in describing the data. The data demonstrated that Maritime cadets’ level of speaking anxiety was moderate level, with average percentage of 58%. Furthermore, communication apprehension was dominant aspect in cadets’ speaking anxiety. Lastly, both the teachers and the students should be aware about English speaking anxiety because somehow it can be a barrier in learning English.